2016
DOI: 10.1002/qua.25337
|View full text |Cite
|
Sign up to set email alerts
|

On the applicability of time‐dependent density functional theory (TDDFT) and semiempirical methods to the computation of excited‐state potential energy surfaces of perylene‐based dye‐aggregates

Abstract: The excited states of perylene-based dye aggregates were investigated with emphasis on the description of the potential energy surfaces for the intermolecular motion in a dimer, which are of importance for exciton trapping. The aim is to investigate the applicability of TDDFT and semiempirical methods. The longitudinal displacement of two p-stacked molecules against each other is used as model and the methods are benchmarked against SCS-CC2 and SCS-ADC(2). Furthermore a simple character analysis is applied. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 59 publications
(163 reference statements)
7
43
2
Order By: Relevance
“…As a result of the interactions between diabatic states, the energy profiles of the two lowest energy adiabatic states (1 B u and 1 A g ) cross several times along the shift coordinate, thereby determining an alternation of the H and J spectroscopic character of the aggregate which is not accounted for by the simpler exciton model. This peculiarity has already been pointed out in previous investigations on PBI dimers and is nicely reproduced at FOCIS level. Concerning the twisting coordinate by comparing diabatic and adiabatic energy profiles we can also identify the presence of an avoided crossing (see Supporting Information Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As a result of the interactions between diabatic states, the energy profiles of the two lowest energy adiabatic states (1 B u and 1 A g ) cross several times along the shift coordinate, thereby determining an alternation of the H and J spectroscopic character of the aggregate which is not accounted for by the simpler exciton model. This peculiarity has already been pointed out in previous investigations on PBI dimers and is nicely reproduced at FOCIS level. Concerning the twisting coordinate by comparing diabatic and adiabatic energy profiles we can also identify the presence of an avoided crossing (see Supporting Information Fig.…”
Section: Resultssupporting
confidence: 81%
“…However, the dimer model, where only two dye molecules out of a larger aggregate are explicitly considered, was employed successfully to obtain parameters of the FE–CT model . Further developments of these models incorporate coarse‐gaining strategies for the determination of coupling parameters between FE and partially also CT‐configurations …”
Section: Introductionmentioning
confidence: 99%
“…84 In previous studies we always used wave-function based approaches like SCS-CC2 because time-dependent density functional theory predicted a different order of the bright Frenkel (S 2 state) and lower CT states (S 3 ). 33,34,85 Using SCS-CC2/TZVP as benchmark, pure GGA (BLYP, PBE) and the hybrid functionals as B3LYP predicted that the CT states should lie considerably below the corresponding Frenkel states, which was in contrast to the predictions of the more accurate SCS-CC2 method. For BHLYP/ TZVP the energy difference between both states were smaller than 0.1 eV but the CT state lie still below the upper Frenkel state.…”
Section: Technical Detailscontrasting
confidence: 39%
“…It is interesting to note that more sophisticated semi-empirical methods as the OMx-approaches of Thiel and coworkers 91,92 seem to be less suitable. 85 More information about these studies can be found in Section 3.6.…”
Section: Technical Detailsmentioning
confidence: 99%
“…[42][43][44] Furthermore, it yields reliable intermolecular potential energies for dimers composed of molecular semiconductors. [45,46] In well-ordered but also in amorphous systems, excitons and charges are expected to be delocalized over several units. [2,47,48] Consequently, the computations of oligomers larger than dimers would be desirable, but such computations are too costly within the framework of the present study.…”
Section: Theoretical Approachmentioning
confidence: 99%